Design Of An Internet Of Thought (Iot)-Based Monitoring Soil And Air Moisture Sensor On Bosai Plants - Revian Setya Nugraha (Sean Institute, 2023)
Soil is an important factor for plant growth and development. Soil conditions that are too dry can inhibit root growth and cause the plant's ability to absorb nutrients. Meanwhile, too wet soil can affect root growth and cause disease in plants. One of the information and communication technologies in engineering is the use of the Internet of Things. Facts in the field are difficult to measure manually. For the value of soil and air humidity is very useful to determine the steps or soil handling. The conclusion of the results shows that measuring humidity using soil and air humidity sensors can work well. But the tool needs to be updated even better to get perfect results. And it can help to monitor bonsai plants via a smartphone so it's easy to monitor at any time to monitor plants. And the average tool works about 17 seconds to get the result.